(untitled) (Texas Journal of Medical Science, 2023)
Since a few years ago, late pregnancies have been a touchy matter in both society and the medical community. In fact, maternal age has been rising for a number of years, with many of these late pregnancies occurring in women between the ages of 40 and 45. According to the World Health Organization (WHO), maternal mental health is a significant factor in determining the morbidity and mortality of both mothers and their children. Objective: This paper aims to assess of health outcomes for pregnancy mothers over age 40 with a statistical evaluation of newborns in Iraq. Patients and Methods: This study has focused on the assessment of assessment of health outcomes for pregnancy mothers where data were collected from health outcomes for pregnancy mothers in different hospitals in Iraq between 4th July 2021 to 6th January 2022, for pregnancy mothers with ages were <30 years and women with ages >40. These data were divided into two kinds of groups where the first one was considered pregnancy women below 35 years with 40 cases while the second one was represented pregnancy women above 40 years with 50 cases. A statistical study was conducted for health outcomes for pregnancy mothers using the SPSS program. Results and Discussion: In our demographic, women over the age of 40 had much higher rates of parity and gravidity than do those under that age. With their higher BMIs and prenatal weight gain, they experience shorter labor phases and a higher frequency of pregnancy problems such as gestational diabetes and hypertension. According to our paper, maternal age is a distinct risk factor for obstetric and neonatal problems. In fact, gestational diabetes, pre-eclampsia, and gestational hypertension were three of the most prevalent conditions associated with pregnancy that multivariate analysis revealed significant findings for. Moreover, Older women appear to be more likely to experience pregnancy problems such as gestational hypertension and diabetes, as well as greater rates of neonatal clavicle fracture and perinatal mortality and caesarean sections. Conclusion: In conclusion, older women appear to be more likely to experience pregnancy issues such as gestational hypertension and diabetes, as well as perinatal mortality, and to require caesarean sections more frequently. Because of this, it is the responsibility of the obstetrician to educate these women, comfort them, and modify the monitoring of their pregnancies in accordance with the risk factors, the method of conception, and the multifetal gestation.